Administrative licensing mechanism as a tool for environmental protection : The building permit model - Azzedine, Wafa (Journal of Human Sciences, 2020)
The protection of the environment in its various frameworks requires procedures, whether preventive or deterrent, which flow in its entirety within the framework of environmental protection laws, and the system  of urban administrative licenses is considered one of the most important effective tribal preventive means to protect the environment as it is a prior mechanism that limits the occurrence of the attack.The system of administrative licenses is also related to the freedoms of private individuals in the construction and construction of what they consider appropriate in their property or what is their powers, and in the rights of society to live in a safe and protected environment, to establish a balance between a public right and a private interest, which is dictated by the privacy and seriousness of the licensing system in general and nature Technical and technical problems of the environment in particular, which keeps the field level applied is the decisive point in the extent of the effectiveness of legal texts for the protection of the environment in the field of administrative licenses.